Risk taking propensity among people involved in various forms of winter recreation on the example of skiing - Iwona Pawelec (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2013)
Nowadays, recreational activity is not only the general tendency to improve physical function, but is also associated with increased physical effort and risk. For example, there has been the development of more sophisticated and dangerous forms of skiing. Today, skiing can be divided into downhill skiing, practiced in ski resorts, and freeskiing. The freeskiing forms include ski-touring and freeride, considered as extreme. The extreme forms are characterized by high risk as the main motive for their practice. The most important predisposition to engage in those activities is the courage expressed in risk taking propensity. Risk taking propensity is a personality trait that affects human decisions in risky situations. Depending on its severity, more or less risky behavior can be observed. The aim of the study was to determine the level of propensity to risk behaviors of people involved in forms of activity associated with a higher risk in comparison with other participants, on the example of recreational skiing. The questionnaire constructed by Ryszard Studenski was used to measure the risk taking propensity and frequency of risky behavior. The research was carried out on 40 persons classified on the basis of the declaration of preferred form of skiing. People practicing extreme forms of winter activity (skitouring, ski-mountaineering) showed lower level of risk taking propensity than a group of downhill skiers. It was found that the preference of risky sports is not definitely related to the higher propensity to risk-taking behavior.